Is a Transdisciplinary Theory of Engagement in Organized Settings Possible? A Concept Analysis of the Literature on Employee Engagement, Consumer Engagement and Patient Engagement - Graffigna, Guendalina (Frontiers in Psychology, 2017)
Organizations are experiencing increased competition, disruptive innovation and continuous changes in their social and economic context. Furthermore, the decrease of resources (economic and human) in such a demanding context make it imperative for organizations finding new models and strategies to make their service delivery better sustainable at the economic, environmental and psychological level. In such a complex scenario the concept of engagement of the individuals implied in organized settings (either as a service provider or as a final receiver) is taking space as a promising lever for innovation. However, despite the number of contributes retrievable, the debate about engagement is still very fragmented because the corpus of literature approaching the different area of engagement is divided and diverse in its nature. In the present contribute we discuss the results of a conceptual analysis of the literature in order to investigate overlapping features and areas of divergence among three different areas of investigation and application of the engagement phenomenon in organized setting: the domains of employee engagement, consumer engagement and patient engagement, purposively selected as prototypical of the phenomenon of engagement along the “inside”-“outside” of organizational settings. This study consisted on a qualitative conceptual analysis of scholarly literature indexed with the key terms “employee engagement”, “consumer engagement” and “patient engagement”. We performed a key-word based research strategy of the literature in the Scopus database. A total of 163 articles were selected and analyzed. The analysis casted light on the following areas of conceptual overlapping among employee, consumer and patient engagement: 1) engagement is diverse from the concept of empowerment and activation; 2) engagement is a multi-componential psychological experience; 3) engagement is a self-transformative experience; 4) engagement develops within a relational context; 5) engagement is a systemic phenomenon. These findings, although preliminary and needing further investigation, suggest the feasibility of promoting a transdisciplinary reflection about the phenomenon of engagement in organized setting.